2022
DOI: 10.1177/03915603221142665
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin as prognostic factor in patients with Fournier’s gangrene

Abstract: Introduction: Fournier’s Gangrene (FG) has still a mortality rate up to 45%. Several studies identified prognostic factors but there is a knowledge gap concerning procalcitonin (PCT) levels and mortality risk in FG. This study is aimed to assess the role of PCT as prognostic factor in FG. Materials and methods: The medical records of 20 male FG patients admitted at the Department of Urology of “Cattinara” Hospital, University of Trieste between January 2019 and November 2020 were retrospectively reviewed. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Of those, nine were excluded, with reasons. Finally, the remaining 40 articles [ 6 , 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], comprising a total of 2257 patients, were considered for our systematic review and meta-analysis. The main characteristics of the included studies are detailed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of those, nine were excluded, with reasons. Finally, the remaining 40 articles [ 6 , 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], comprising a total of 2257 patients, were considered for our systematic review and meta-analysis. The main characteristics of the included studies are detailed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 37 studies [ 6 , 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 45 , 47 , 48 ] comprising 2043 patients with FG and evaluable FGSI data at admission were compared between survivors and non-survivors. The pooled analysis showed that the non-survivor cohorts exhibited higher FGSI values than the survivors (MD: 5.53, 95% CI: 4.68–6.37) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation